Geochemistry of late miocene-pleistocene basalts in the Phu Quy island area (East Vietnam Sea): Implication for mantle source feature and melt generation - Anh*, Le Duc; Hoang, Nguyen; Shakirov, Renat B.; Huong, Tran Thi (Vietnam Journal of Earth Sciences, 2017)
The chemical compositions of late Miocene - Pleistocene basalts in Phu Quy island defines two major geochemical groups that reflect the formation and development of the island. The early low alkaline, TiO2 and P2O5, and high SiO2 group, comprising olivine and tholeiitic basalts, forms the base of the island. The later high alkaline, TiO2, and P2O5, and low SiO2 group, produced by central-type volcanic eruptions consisting of alkaline olivine and olivine basalts, overlies the early eruptive group. Crustal contamination may be expressed by the positive correlation between Ba/Nb and SiO2, which are higher in early eruptive basalts, possibly reflecting the involvement of crustal material, either in the source region or interaction of the melt on the way to the surface. However, negative relationship between Ba and SiO2, and positive correlation between Nb/Y and Zr/Y observed for two basaltic series may reflect the effect of melting pressures and degrees of partial melting. Methods of calculating the primitive basaltic melts based on the principle of olivine incremental additions to the basalt until the composition is equilibrated with the residual olivine at Fo89-90 may be used. The computed results show that the early basalts were generated under pressures of about 18-20 Kb (ca. 55-60 km) and the later basalts were formed in the pressure range of 20 to 25 Kb (corresponding to the depths about 60 to 75 km). The close range of melting pressures suggests decompression polybaric melting of a mantle source, which allows for mixing of various melt portions, resulting in the formation of geochemically linear relationship. It has been demonstrated that the post-opening volcanism was unrelated to an important tectonic phase and that the calculated extension factor (b) for the regional major extension fault systems is not significant (ca. 1.3) to trigger mantle melting. Therefore, the infiltration of asthenospheric flows resulting from the Neo-Tethys closure following the collision between India and Eurasia in the late Tertiary, may not only raise the mantle temperature leading to the melting but also appear to be the major driving force of marginal sea opening in the western Pacific, including the East Vietnam Sea. References Baker M.B., Hirschmann M.M., Ghiorso M.S., Stolper E.M., 1995. Compositions of near-solidus peridotite melts from experiments and thermodynamic calculations. Nature 375, 308-311. Baker M.B., Stolper E.M., 1994. Determining the composition of high pressure mantle melts using diamond aggregates. Geochimica et Cosmochimica Acta 58, 2811-2827. Carter A., Roques D., Bristow C.S., 2000. Denudation history of onshore central Vietnam: constraints on the Cenozoic evolution of the western margin of the South China Sea. Tectonophysics 322, 265-277. Ding W., Li J., Clift P.D., & Expedition I.O.D.P., 2016. Spreading dynamics and sedimentary process of the Southwest Sub-basin, South China Sea: constraints from multi-channel seismic data and IODP Expedition 349. Journal of Asian Earth Sciences, 115, 97-113. Fitton J.G., Saunders A.D., Norry M.J., Hardarson B.S., Taylor R.N., 1997. Thermal and chemical structure of the Iceland plume. Earth and Planetary Science Letters 153, 197-208. Flower M.F.J., Zhang M., Tu K., Xie G.H., Chen C.Y., 1992. Magmatism in the South China Basin 2.Post-spreading Quaternary basalts from Hainan Island, south China. Chemical Geology 97, 65-87. Flower M., Tamaki K., Hoang N., 1998. Mantle Extrusion: A model for Dispersed Volcanism and DUPAL-like Asthenosphere in East Asia and the Western Pacific. In: Mantle dynamics and plate Interactions in East Asia, edited by: Flower, M et al. Geodynamic 27, 67-88. Flower M.F.J., Russo R.M., Tamaki K., Hoang Nguyen, 2001. Mantle contamination and the Izu-Bonin-Mariana (IBM) ‘high-tide mark’, evidence for mantle extrusion caused by Tethyan closure. Tectonophysics 333, 9-34. Franke D., Savva D., Pubellier M., Steuer S., Mouly B., Auxietre J.L., Meresse F., Chamot L.R., 2013. The final rifting evolution in the South China Sea. Marine and Petroleum Geology xxx, 1-17. Fyhn M.B.W., Boldreel L.O., Nielsen L.H., 2009. Geological development of the Central and South Vietnamese margin: implications for the establishment of the South China Sea, Indochinese escape tectonics and Cenozoic volcanism. J. Tectonophysics, 478 (3-4), 184-214. Hirose K., Kushiro I., 1993. Partial melting of dry peridotites at high pressures: determination of compositions of melts segregated from peridotite using aggregates of diamond. Earth and Planetary Science Letters 114, 477-489. Hofmann A.W., 1988. Chemical differentiation of the Earth: the relationship between mantle, continental crust, and oceanic crust. Earth and Planetary Science Letters 90, 297-314. Kamenetski V.S., Chung S.-L., Kamenetski M.B., Kuzmin D.V., 2012. Picrites from the Emeishan large igneous province, SW China: a compositional continuum in primitive magmas and their respective mantle sources. Journal of Petrology 53 (N10), 2095-2113. Kogiso T., Hirose K., Takahashi E., 1998. Melting experiments on homogeneous mixtures of peridotite and basalt: Application to the genesis of ocean island basalts. Earth and Planetary Science Letters 162, 45-61. Koloskov A.V., 1999. Ultrabasic inclusions and volcanics as a self-regulated geologic system. Nauchnyi Mir, Moscow (in Russian). Koloskov A.V., Fedorov P.I., Rashidov V.A., 2016. New data on products composition of the Quaternary volcanic activity in the shelf zone of NW margins of the South China Sea and the problem of asthenospheric diapirism. Koloskov A.V., Flerov G. B., Sharas’kin A. Y., 1989. Rift-Related Volcanism in the System of Eastern Asian Volcanic Belts. In Magmatism of Rifts: Petrology, Evolution, Geodynamics, Ed. by O. A. Bogatikov, Nauka, Moscow, 139-144 (in Russian). Koloskov A.V., Rashidov,V. A., Gatinskii Y. G., et al., 2003. Late Cenozoic volcanism in the continental shelf zones of Vietnam. In Proceedings of the Annual Conference Devoted to the Day of Volcanologists. Naukadlya Kamchatki, Petropavlovsk Kamchatskii, 9-15 (in Russian). Kudrass H. R., Hiedicke M., Cepek P., Kreuzer H., and Müller P., 1986. Mesozoic and Cenozoic rocks dredged from the South China Sea (Reed Bank area) and Sulu Sea and their significance for plate tectonic reconstructions. Mar. Pet. Geol.3, 19-30. Kushiro I., 1990. Partial melting of mantle wedge and evolution of island arc crust. Journal of Geophysical Research 95, 15929-15939. Kushiro I., 1996. Partial melting of a fertile mantle peridotite at high pressures: An experimental study using aggregates of diamond. In Basu A., and Hart S., eds. Earth processes: Reading the isotopic clock: American Geophysical Union Geophysical Monograph 95, 109-122. Kushiro I., 1998. Compositions of partial melts formed in mantle peridotites at high pressures and their relation to those of primitive MORB. Physics of the Earth and Planetary Interiors 107, 103-110. Latin D., White N., 1990. Generating melt during lithospheric extension: uniform vs. simple shear. Geology 18, 327-331. Le Bas M.J., Le Maitre R.W., Streckeisen A., Zanettin B., 1986. A chemical classification of volcanic rocks based on the total alkali-silica diagram. Journal of Petrology 27, 745-750. Le Duc Anh, Nguyen Hoang, 2017. Geochemistry of Cenozoic basalts in the south-Central Vietnam coastline region: implications for regional mantle - lithosphere interaction. Vietnam Journal of Earth Sciences, in preparation. Lee T.Y., Lo C-H., Chung S-L., Chen C-Y., Wang L., Lin W-P., Nguyen Hoang, Cung Thuong Chi, Nguyen Trong, Yem, 1998. 40Ar/39Ar dating result of Neogene basalts in Vietnam and its tectonic implication. In: Flower, M.F.J., et al. (Eds.), Mantle Dynamics and Plate Interactions in East Asia. Geodynamics Series, vol. 27, American Geophysics Union, 317-330. Li C.-F., et al., 2014. Ages and magnetic structures of the South China Sea constrained by deep tow magnetic surveys and IODP Expedition 349, Geochem. Geophys. Geosys., 15, 4958-4983. Li C-F., et al., 2015. Seismic stratigraphy of the central South China Sea basin and implications for neotectonics. J. Geophys. Res. Solid Earth, 120, 1377-1399. Doi:10.1002/2014JB011686. Li C.-F., Lin J., Kulhanek D.K., 2013. South China Sea tectonics: Opening of the South China Sea and its implications for southeast Asian tectonics, climates, and deep mantle processes since the late Mesozoic, IODP SCI. Prosp., 349. Li L., Clift P., Nguyen The Hung, 2013. The sedimentary, magmatic and tectonic evolution of the southwestern South China Sea revealed by seismic stratigraphic analysis. Marine Geophysical Research 34, 341-365. Li L., Clift P.D., Stephenson R., Nguyen T.H., 2014. Non-uniform hyper-extension in advance of seafloor spreading on the Vietnam continental margin and the SW South China Sea. Basin Research 26, 106-134. Malinovsky A.I., Rashidov V.A., 2015. Compositional characteristics of sedimentary and volcano-sedimentary rocks of Phu Quy-Catwickisland group in the continental shelf of Vietnam. Bulletin of Kamchatka Regional Association of ‘Educational - Scientific’ Center, Earth Sciences 27 (3), 12-34 (in Russian with English summary). McKenzie D., Bickle M.J., 1988. The volume and composition of melt generated by extension of the lithosphere. Journal of Petrology 26, 625-679. McKenzie D., O’Nions R.K., 1991. Partial melt distribution from inversion of rare earth element concentrations. Journal of Petrology 32, 1021-1091. Nguyen Hoang, 2005a. Source characteristics and melting conditions of Cenozoic basalts from Pleiku, south-central Vietnam. Journal of Geology Series A 286, 15-22 (in Vietnamese with English abstract). Nguyen Hoang, 2005b. Lithospheric mantle beneath Pleiku: evidence from mantle xenolith. Journal of Geology Series A 287, 8-19 (in Vietnamese with English abstract). Nguyen Hoang, Flower M.F.J., 1998. Petrogenesis of Cenozoic basalts from Vietnam: implication for origins of a diffuse igneous province. J. Petrol. 39, 369-395. Nguyen Hoang, Flower M.F.J., Carlson R.W., 1996. Major, trace element, and isotopic compositions of Vietnamese basalts: interaction of enriched mobile asthenosphere with the continental lithosphere? Geochimica et Cosmochimica Acta 60, 4329-4351. Nguyen Hoang, Uto K., 2003. Geochemistry of Cenozoic basalts in the Fukuoka district (northern Kyushu, Japan), implications for asthenosphere and lithospheric mantle interaction. Chemical Geology 198, 249-268. Nguyen Hoang, Phan Trong Trinh, 2009. Overview of petrologic and geochemical characteristics of Neogene-Quaternary basalts in the East Vietnam Sea and neighboring regions and their related mantle dynamics. Journal of Geology, 312A, 39-57 (in Vietnamese with English abstract). Nguyen Hoang, Flower M.F.J., Cung Thuong Chi, Pham Tich Xuan, Hoang Van Quy, Tran Thanh Son, 2013. Collision-induced basalt eruptions at Pleiku and Buon Me Thuot, south-central Viet Nam. Journal of Geodynamics 69, 65-83. Nguyen Hoang, Ogasawara M., Tran Thi Huong, Phan Van Hung, Nguyen Thi Thu, Cu Sy Thang, Pham Thanh Dang, Pham Tich Xuan, 2014. Geochemistry of Neogene basalts in the Nghia Dan district, western Nghe An. Vietnam Journal of Earth Sciences 36(4), 403-412. DOI: 10.15625/0866-7187/36/4/6428. Nguyen Hoang, Tran Thi Huong, Ogasawara M., Le Duc Anh, Nguyen Thi Mai, Nguyen Thi Thu, Cu Sy Thang, Le Thi Phuong Dung, 2016. Petrography and geochemistry of Permian basalts of the Cam Thuy formation and their relation to Song Da and Emeishan magmatic rocks. Vietnam Journal of Earth Sciences 38, 372-392. DOI: 10.15625/0866-7187/38/4/8993. Nguyen Nhu Trung, Lee S.M., Bui Cong Que, 2004. Satellite gravity anomalies and their correlation with the major tectonic features in the South China Sea. Gondwana Research 7(2), 407-424. Nguyen Nhu Trung, Nguyen Thi Thanh Huong, 2013. Topography of the Moho and Earth crust structure beneath the East Vietnam Sea from 3D inversion of granite field data. Acta Physica 61(2), 357-384. Norman M.D, Garcia M.O., 1999. Primitive magmas and source characteristics of the Hawaiian plume: petrology and geochemistry of shield picrites. Earth and Planetary Science Letters 168, 27-44. Pearce J.A., Norry M.J., 1979. Petrogenetic implications of Ti, Zr, Y, and Nb variations in volcanic rocks. Contributions to Mineralogy and Petrology 69, 33-47. Rangin C. Huchon, Le Pichon X., Bellon H., Lepvrier C., Roques D., Hoe N.D., Quynh V., 1995. Cenozoic deformation of central and south Vietnam. Tectonophysics 251, 179-196. Regelous M., Niu Y., Wendt J.I., Batiza R., Greig A., Collerson K.D., 1999. Variations in the geochemistry of magmatism on the East Pacific Rise at 10°30’N since 800 ka. Earth Planet. Sci. Lett. 168, 45-63. Roeder P.L., Emslie R.F., 1970. Olivine-liquid Equilibrium. Contributions to Mineralogy and Petrology 29, 275-289. Ru K., Pigott J.D., 1986. Episodic rifting and subsidence in the South China Sea. AAPG Bull 70(9), 1136-1155. Rudnik R.L., Fontaine D.M., 1995. Nature and composition of the continental crust: a lower crustal perspective. Review Geophysics, 33, 267-309. Sava D., Pubellier M., Franke D., Chamot-Rooke N., Meresse F., Steuer S., Auxietre J.L., 2014. Different expressions of rifting on the South China Sea margins. Marine and Petroleum Geology 58, 579-598. Scarrow, J. H., Cox, K. G., 1995. Basalts generated by decompressive adiabatic melting of a mantle plume: a case study from the Isle of Skye, NW Scotland. Journal of Petrology 36, 3-22. Sun S.S., McDonough W.F., 1989. Chemical and isotopic systematics of oceanic basalts: implications for mantle composition and processes. In: Saunders, A.D., Norry, M.J. Eds. Magmatism in Ocean Basins. Geol. Soc. Spec. Publ., London, 313-345. Takahashi E., Kushiro I., 1983. Melting of a dry peridotite at high pressures and basalt magma genesis. American Mineralogist 68(9-10), 859-879. Tamaki K., 1995. Upper mantle extrusion tectonics of southeast Asia and formation of western Pacific backarc basins. In: International Workshop: Cenozoic Evolution of the Indochina Peninsula, Hanoi/Do Son, April, p.89 (Abstract with Programs). Taylor S.R., McLennan S.M., 1985. The continental crust: Its composition and evolution.Blackwell Scientific Publishers, Oxford. Tran Duc Luong, Nguyen Xuan Bao, 1981. Geological map 1:500.000 of Vietnam. Tu K., Flower M.F.J., Carlson R.W., Zhang M., Xie G.-H., 1991. Sr, Nd, and Pb isotopic compositions of Hainan basalts (South China), implications for a subcontinental lithosphere DUPAL source. Geology 19(6), 567-569. Tu K., Flower M.F.J., Carlson R.W., Zhang M., Xie G.H., 1992. Magmatism in the South China Basin, 1.Isotopic and trace element evidence for an endogenous Dupal mantle component. Chemical Geology 97, 47-63. Turner S., Hawkesworth C., 1995. The nature of the sub-continental mantle: constraints from the major element composition of continental flood basalts. Chemical Geology 120, 295-314. Walker D., Shibata T., DeLong D.E., 1979. Abyssal tholeiites from the Oceanographer Fracture Zone III. Phase equilibria and mixing. Contributions to Mineralogy and Petrology 70, 111-125. Yamashita S., Tatsumi Y., Nohda S., 1996. Temporal variation in primary magma compositions in the northeast Japan Arc, The Island Arc5, 276-288. Yan Q., Shi X., Castillo R.B., 2014. The late Mesozoic-Cenozoic tectonic evolution of the South China Sea: A petrologic perspective. Journal of Asian Earth Sciences 85, 178-201. Yang Y., Liu M., 2009. Crustal thickening and lateral extrusion during the Indo-Asian collision: a 3D viscous flow model. Tectonophysics 465, 128-135. Zhou P., Mukasa S., 1997. Nd-Sr-Pb isotopic, and major- and trace-element geochemistry of Cenozoic lavas from the Khorat Plateau, Thailand, sources and petrogenesis. Chemical Geology 137, 175-193.